Interaction between Zygosaccharomyces bailii and Schizosaccharomyces pombe enhances acetic acid reduction in Baijiu fermentation - Shuai Yuan; Yuan Yun; Zhiguo Liu; Shuang Xing; Jiajun Du; Qinghe Liu; Mingjian He; Jinqi Guo; Liangcai Lin; Cuiying Zhang (Food Research International, 2026)

Mutual information guided domain adaptation network for unsupervised transfer fault diagnosis of offshore wind turbines under time-varying conditions and scarce labels - Yun Kong; Guoyu Huang; Cuiying Lin; Haiqiang Wang; Qinkai Han; Junyu Qi; Hui Liu; Fulei Chu (Ocean Engineering, 2026)

Deciphering the mechanism underlying the n-propanol accumulation in Baijiu fermentation: A novel perspective from the interplay between acetic acid and microbial metabolism - Shuang Xing; Yapan Zhang; Boyuan Hu; Qinghe Liu; Jiayu Zhang; Shuai Yuan; Shiming Shen; Tianyu Pang; Mingjian He; Yuan Yun; Liangcai Lin; Cuiying Zhang (Food Bioscience, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Digital transformation of Jiangxiangxing Baijiu production: integrating flavor compound analysis, machine learning recognition, and genetic algorithm blending of multi-rounds - Xiaotong Lyu; Qi Jiang; Kemin Linghu; Yifei Zhou; Mengqian Yu; Chunhui Wei; Liangcai Lin; Qi Zhou; Zhengshu Zhou; Cuiying Zhang (Food Research International, 2026)

Integrated metabolome and transcriptome analyses reveal the seasonal dynamic accumulation and regulation network of benzylisoquinoline alkaloids in Stephania tetrandra roots - Jiqiang Hu; Nannan Tu; Cuiying Lin; Yuzhe Fan; Zhijian Xu; Jianbiao Yao; Su Zeng; Bingxian Yang; Lianli Sun (Food Bioscience, 2026)

Unveiling the yeast interaction: Insights into the role of Saccharomyces cerevisiae metabolites in regulating Torulaspora delbrueckii aroma biosynthesis during wine fermentation - Boqin Zhang; Mengbo Wang; Wenjie Li; Yucui Chen; Xueping Zhao; Chenxi Yu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2025)

Recent advances in analytical approaches for aroma interaction of fermented foods: A review - Xin Li; Gailing Shi; Jia Zheng; Shuang Xing; Lijing Sun; Shiming Shen; Jian Su; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Synergistic exposure to endocrine-disrupting chemicals in pediatric lungs: Epidemiological drivers and disease-associated variations - Chunzhao Chen; Jie Yu; Hui Qi; Cuiying Zhong; Jian Tang; Chenghao Chen; Zheng Li; Xuemei Yang; Yujia Wu; Wanning Chen; Gang Yu; Lin Sun (Environmental Pollution, 2025)

Nickel phthalocyanine-catalyzed ammonia detection on a TiO2 photoelectrochemical sensor with ZIF-67 enrichment for environmental water analysis - Wenru Wu; Nuoxuan Xiong; Yue Lin; Fang Luo; Cuiying Lin; Bin Qiu; Zhenyu Lin; Zhou Jiang; Jian Wang (Water Research, 2025)

Microbiomics and machine learning-assisted approaches reveal amino acid patterns in high-temperature Daqu - Chao Fang; Gailing Shi; Qing He; Shuang Xing; Peng Chen; Feng Shi; Zhiguo Liu; Ping Tang; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Non-volatile compounds as aroma modulators in Jiangxiang-flavor Baijiu: Regional flavor differentiation and synergistic interactions with volatile aromas - Xiaotong Lyu; Meiyi Zhou; Qian Wang; Lihuan Lang; Kemin Linghu; Chunhui Wei; Liangcai Lin; Paul A. Kilmartin; Cuiying Zhang (Food Chemistry, 2025)

One-pot synthesis of highly stable CsPbBr₃@C6H7NO3S composite and its application in nitrite fluorescent sensing - Yongzhen Qiu; Yexin Zu; Yating Zhang; Yue Lin; Fang Luo; Zuquan Weng; Cuiying Lin; Jian Wang; Bin Qiu; Zhenyu Lin (Food Chemistry, 2025)

Dietary trehalose reduced liver glycogen accumulation and promoted protein deposition in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed a high-carbohydrate diet - Yi Xiao; Xingbo Su; Jiaying Xie; Huiwen Zhang; Qiming Huang; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

A complex function model for foundation pit slope excavation, incorporating stress interaction among densely karst caves in the underground space - Zhen Liu; Jin Liao; Yongtao Wu; Chunxiu Lin; Liang Zeng; Cuiying Zhou (Engineering Geology, 2025)

The discrepancy in amino acids within high-temperature Daqu: A novel metabolic marker for the quality evaluation of Daqu - Shuang Xing; Gailing Shi; Jun Lu; Chao Fang; Changwen Li; Shuai Yuan; Feng Shi; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Docosahexaenoic acid alleviated liver lipid deposition and health damage induced by cholesterol accumulation in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Qiming Huang; Huiwen Zhang; Xingbo Su; Yi Xiao; Jiaying Xie; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Distinct ultrafast dynamics of bilayer and trilayer nickelate superconductors regarding the density-wave-like transitions - Yidian Li; Yantao Cao; Liangyang Liu; Pai Peng; Hao Lin; Cuiying Pei; Mingxin Zhang; Heng Wu; Xian Du; Wenxuan Zhao; Kaiyi Zhai; Xuefeng Zhang; et al. (Science Bulletin, 2025)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

Unraveling the chemosensory characteristics dependence of sauce-flavor baijiu on regionality using descriptive sensory analysis and quantitative targeted flavoromics - Xin Li; Busheng Zhang; Wenxuan Li; Yawen Zhao; Xiaotong Lyu; Xiaolong You; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2024)

Using in situ untargeted flavoromics analysis to unravel the empty cup aroma of Jiangxiang-type Baijiu: A novel strategy for geographical origin traceability - Busheng Zhang; Liangcai Lin; Canjie Zheng; Xuan Liu; Wanjing Cui; Xin Li; Xiaotong Lyu; Cuiying Zhang (Food Chemistry, 2024)

Identification of a novel crustacean vascular endothelial growth factor b-like in the mud crab Scylla paramamosain, and examination of its role in lipid accumulation - Wenjie Zhong; Chuangsi Chen; Senyue Tan; Xianda He; Shuqi Wang; Douglas R. Tocher; Fan Lin; Zhijie Sun; Xiaobo Wen; Yuanyou Li; Khor Waiho; Xugan Wu; et al. (Aquaculture, 2023)

Oxygen-induced dual-signal point-of-care testing aptasensor for aflatoxin B1 detection using platinum nanoparticle catalysis in visual fluorometry and gravimetry - Fang Luo; Linxiu Zhan; Ye Deng; Kun Qiao; Nan Pan; Zuquan Weng; Cuiying Lin; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2023)

Differences in lipid accumulation and mobilization in the hepatopancreas and ovary of female mud crab (Scylla paramamosain, Estampador, 1949) during ovarian development - Baojia Chen; Jia Zheng; Cuiying Chen; Kun Wu; Fan Lin; Lijun Ning; Hua Rong; Chuan Chen; Fei Xiao; Haotian Zhang; Xiaobo Wen (Aquaculture, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Simulated Short- and Long-Term Deformation in Coastal Karst Caves - Chunxiu Lin; Chang Xia; Hong Zhang; Zhen Liu; Cuiying Zhou (Journal of Marine Science and Engineering, 2022)
The self-balanced pressure arch theory is an important basis for excavation support in karst caves, but it is difficult to quantify the empirical theory in coastal areas. In addition, the rheological effects of karst strata could pose a hazard to engineering. Therefore, this study investigated the rheological mechanism under the self-balanced pressure arch effect, and we proposed a mesoscopic unit rheological model for clay minerals in a water-rich environment. With the discrete element method (DEM), we realized the numerical modeling of the rheological model. Then, the proposed model is validated by a case study of foundation excavation in the coastal karst area of China. The mesoscopic mechanical characteristics of caves considering the influence of pressure arch are analyzed. The results show that the self-balance of the caverns mainly lies in the mesoscopic mineral strength and local stress. With the rheological controlled model, the final predicted convergent deformation of the foundation has an error of less than 10% compared with the field monitoring data. In this study, we can quantitively describe the self-balance effect of the pressure arch surrounding the caves and reveal the rheological mechanism. The proposed model can be applied to similar engineering with careful calibration and provide safety guidance.

Dietary calcium pyruvate could improve growth performance and reduce excessive lipid deposition in juvenile golden pompano (Trachinotus ovatus) fed a high fat diet - Yiru Shao; Zhiyong Xie; Shusheng Liang; Cuiying Chen; Douglas R. Tocher; Li Lin; Yanhua Huang; Yuanyou Li; Dizhi Xie; Yucong Hong; Shuqi Wang; Cuihong You (Fish Physiology and Biochemistry, 2022)

A Comprehensive Correlation Study of Structured Soils in Coastal Area of South China about Structural Characteristics - Chunxiu Lin; Chang Xia; Zhen Liu; Cuiying Zhou (Journal of Marine Science and Engineering, 2022)
Granite residual soil is a common engineering material, and its mechanical properties are of great importance to engineering safety. This kind of soil presents obvious structural characteristics, and many researchers have emphasized the significance of its structural features. According to previous experiments, from a macroscopic perspective, many researchers have investigated the structural relationship between undisturbed and remolded soils, but few studies have considered it in the mesoscopic aspect. Adopting DEM (a mesomechanical simulation method), we can study how the structure affects the mechanical process between undisturbed and remolded soil. Therefore, this paper combines DEM with laboratory tests to study the structural characteristic correlation between undisturbed and remolded soil. The results indicate that a weak cohesion effect exists in undisturbed soil, and the damage of weak cohesion elements accompanies the failure process. Weak cohesion elements in undisturbed soil cause inhomogeneities in deformation, stress state, and damage accumulation, which ultimately causes differences in strength curves. This paper explains the mechanism of the structural effect on mechanical evolution from a mesomechanical perspective. The DEM simulation method proposed in this paper can be applied to structured soils and better guide engineering practice.

Effect of jet airflow deflection on cleaning performance of filter cartridge - Ling Ren; Na Yuan; Longyuan Lin; Chunhong He; Cuiying Tang; Zhiyong Xu (Environmental Science and Pollution Research, 2022)